“You just nod and pin and sew and let them do their thing”: An Analysis of the Wedding Dress as an Artifact and Signifier - Walsh, Kristin (Ethnologies, 2005)
The bridal gown is perhaps one of the most highly symbolic objects in the contemporary wedding ceremony. Fraught with images of sexuality and femininity, the bride conveys multiple messages with her choice of dress colour, style and adornment. As such, the dress communicates and performs as a significant material culture object within the custom of the wedding. This article examines the wedding dress within the North American context through the experiences of Nancy Harris, a dressmaker. The author discusses the struggles of the bride as she negotiates with family, friends and societal conventions while expressing herself through her choice of dress.